Post-marketing safety surveillance for both CRM197 and TT carrier proteins PCV13 in Jiangsu, China - Hu, Ran; Liu, Yuanbao; Zhang, Lei; Kang, Guodong; Xu, Borong; Li, Mingma; Yu, Jing; Zhu, Yuanyuan; Guo, Hongxiong; Wang, Zhiguo (Frontiers in Public Health, 2023)
Background This study is to evaluate the safety of two kinds of PCV13 carriers by monitoring the occurrence of adverse event following immunization (AEFI) after the launch of two kinds of PCV13 carriers in Jiangsu Province, China. Methods The AEFI Information System (CNAEFIS) of mainland China was used to monitor the incidence and classification of adverse reactions of the CRM197-carrier protein PCV13 and TT-carrier protein PCV13 vaccines. Results There was no statistical difference between the cumulative reported incidence of AEFI between the two vaccines from 2020 to 2022 (χ2 = 1.991, p < 0.158). 96.62% of the AEFIs were classified as common reactions; rare reactions and coincidental events only accounted for 2.99 and 0.39% of all the AEFI cases, respectively. Redness (2.6 cm–5 cm) is the commonest symptom at the injection site for both vaccines. More than 97% of AEFIs occurred between 30 min and 3 days after administration for both types of PCV13. Conclusion Both vaccines perform well in terms of safety. We did not identify any new/unexpected safety concern from the NAEFISS during a 4 years timespan.